Academic Research and Reform: A History of the Empirical Basis for NCAA Academic Policy - Petr, Todd A.; McArdle, John J. (Journal of Intercollegiate Sport, 2012)
The purpose of this article is to provide an historical overview of the National Collegiate Athletic Association’s (NCAA) academic reform, with a particular focus on the empirical basis for the decisions made. The authors outline four eras of academic reform, examine the types of information the NCAA has collected and used to make decisions about academic policy, and explore the limits of such academic data.